Effects of Replacement of Dietary Fishmeal by Cottonseed Protein Concentrate on Growth Performance, Liver Health, and Intestinal Histology of Largemouth Bass (Micropterus salmoides) - Liu, Yulong; Lu, Qisheng; Xi, Longwei; Gong, Yulong; Su, Jingzhi; Han, Dong; Zhang, Zhimin; Liu, Haokun; Jin, Junyan; Yang, Yunxia; Zhu, Xiaoming; Xie, Shouqi (Frontiers in Physiology, 2021)
An 8-week feeding trail was conducted to explore the effects of replacement of fishmeal by cottonseed protein concentrate (CPC) on growth performance, antioxidant indices and healthy status of largemouth bass. Four isonitrogenous and isolipid diets were formulated to include 0 g/kg, 111 g/kg, 222 g/kg, 333 g/kg of cottonseed protein concentrate, corresponding to replace 0% (D1), 25% (D2), 50% (D3) and 75% (D4) of fishmeal. 240 largemouth bass (15.11±0.02g) were randomly divided into 4 groups with 3 tanks per group. During the experiment, fish were fed to apparent satiety twice daily. Results indicated that CPC could replace up to 50% fishmeal in diet for largemouth bass without significant adverse effects on growth performance. However, weight gain rate (WGR), specific growth rate (SGR), feed efficiency (FE) and condition factor (CF) of largemouth bass were significantly decreased when 75% of dietary fishmeal was replaced by CPC. The whole-body lipid content was increased with the increasing dietary CPC levels. Oil red O staining results indicated that fish fed D4 diet showed an aggravated fat deposition in liver tissues. Hepatocytes exhibited seriously degeneration, volume shrinkage and inflammatory cells infiltration in D4 group. Intestinal villi appeared shorter and sparse with severe epithelial damage in D4 group. Transcriptional level of anti-inflammatory cytokines including tgf-β, il-10 and il-11β were down-regulated in D4 group. The lipid metabolism-related genes (cpt1, pparα) and TOR pathway genes (tor, s6) were also significantly down-regulated in D4 group. It was concluded that suitable replacement of fishmeal by less than 222g CPC /kg diet had a positive effect on growth performance of fish, but an excessive substitution of 75% fishmeal by CPC would lead to the suppressed growth, liver and intestinal damage of largemouth bass.